Chance and determinism in Avicenna and Averroes - Belo, Catarina, 1974- (Islamic philosophy, theology, and science, 2007)
Examines the question as to whether medieval Muslim philosophers Avicenna (Arabic Ibn Sina 980-1037) and Averroes (Arabic Ibn Rushd 1126-1198) are determinists. With a focus on physics and metaphysics, this book also studies their views on chance events in nature, as well as matter, in particular prime matter, and divine providence.